2012
DOI: 10.1111/j.1472-765x.2012.03299.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory expression of a β-xylosidase gene fromThermomyces lanuginosusinEscherichia coliand characterization of its recombinant enzyme

Abstract: Aims:  To characterize a β‐xylosidase from the thermophilic fungus Thermomyces lanuginosus and to investigate its potential in saccharification of hemicellulosic xylans. Methods and Results:  A gene (designated TlXyl43) encoding β‐xylosidase was cloned from T. lanuginosus CAU44 and expressed in Escherichia coli. The gene consists of a 1017‐bp open reading frame without introns. It encodes a mature protein of 338 residues with no predicted signal peptide, belonging to glycoside hydrolase (GH) family 43. Over 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Based on the Lineweaver-Burk plots, the calculated Km and Vmax of the Xyl43 using the p NPX as substrate were 4.05 mM and 88.82 μmol min −1 mg −1 , respectively. Table 1 showed the Xyl43 had significantly lower Km values than the β-xylosidases from Humicola insolens (12.2 mM) 6 , Paecilomyces thermophile (8 mM) 17 , Neurospora crassa (8.9 mM) 24 , but similar to the β-xylosidases reported from Thermomyces lanuginosus and Paecilomyces thermophile 13 , 20 . Moreover, this recombinant Xyl43 exhibited higher Vmax toward p NPX than that of some β-xylosidases reported.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Based on the Lineweaver-Burk plots, the calculated Km and Vmax of the Xyl43 using the p NPX as substrate were 4.05 mM and 88.82 μmol min −1 mg −1 , respectively. Table 1 showed the Xyl43 had significantly lower Km values than the β-xylosidases from Humicola insolens (12.2 mM) 6 , Paecilomyces thermophile (8 mM) 17 , Neurospora crassa (8.9 mM) 24 , but similar to the β-xylosidases reported from Thermomyces lanuginosus and Paecilomyces thermophile 13 , 20 . Moreover, this recombinant Xyl43 exhibited higher Vmax toward p NPX than that of some β-xylosidases reported.…”
Section: Resultssupporting
confidence: 51%
“…1 ) were described and characterized now. Most of the known fungal β-xylosidases from GH 43 were greatly tolerant to xylose, for example, Xyl43A and Xyl43B with the Ki values of 79 mM and 292 mM from Humicola insolens respectively 6 , TlXyl43 with the Ki value of 63 mM from Thermomyces lanuginosus 13 , PtXyl43 with the Ki value of 139 mM from Paecilomyces thermophile 14 . These β-xylosidases without predicting signal peptides were expressed in Escherichia coli ( E .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that some β-xylosidases experience end-product inhibition by xylose present in the reaction mix [ 15 , 25 ]. We have observed a similar effect on XynB where its relative activity quickly dropped to 55 % in the presence of 20 mM of xylose and continued decreasing with increasing xylose concentration in the reaction mix (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial enzymes are mostly expressed heterologously in E. coli (Teng et al 2011) but fungal enzymes are generally purified from their original cultures (Ohta et al 2010) or produced in different high-level expression systems such as Aspergillus (Kitamoto et al 1999) or P. pastoris (Chen et al 2012b). With methanol induction a β-Xylosidase (Xyl3A) from Humicola insolens Y1 was successfully overexpressed in P. pastoris GS115 without signal peptide (Xia et al 2015) and the secretion of enzyme was facilitated by using the signal peptide of the yeast α-factor into the culture supernatant.…”
Section: Expression Of β-Xylosidase Genesmentioning
confidence: 99%